Diplomacy of the project "Economic belt of the Great Silk Road" in modern foreign policy of China - Hasparian, Ye.; Karlyuk, S. V. (Харківський національний університет ім. В. Н. Каразіна, 2019)
The authors consider the Chinese policies of promoting the Silk Road Economic Belt project as a means of expansion of China’s influence on the global scale in general and as a means to find new markets for its goods. China’s strategies to implement its project are viewed.
Keywords: Eurasian cooperation; free trade economic areas; megaproject; Silk Road